MSMEs Resilience During Post-Pandemic through Business Digitalization Mediated by Competitive Advantage - Pambreni, Yuni; Ayu Sudari, Suci (DAS Institute, 2025)
During post-covid-19 pandemic, MSMEs in Indonesia are experiencing difficult times. Based on a BI survey, as many as 87.5% of MSMEs experienced a decline in sales, and the remaining 12.5% were not affected and tended to experience an increase because they were able to be resilient and adapt by digitalizing their business. In facing digital transformation, MSMEs often encounter 3 main challenges, including low technological knowledge, difficulty finding suitable digital platforms, and not being able to determine the right digital marketing strategy. This research aims to analyze the mediation of competitive ability on business digitalization as an effort to increase the resilience of Sukmajaya MSMEs after the Covid-19 pandemic. The analysis method used is path analysis. Business digitalization as an independent variable with indicators namely cost, incentive program, site design, and interactive. Competitive advantage as an intervening/mediating variable with indicators including, business networks, innovation, differentiation. Then, the dependent variable is MSME resilience with measurement indicators, namely problem solving and toughness. The unit of analysis in this research is MSMEs in Sukmajaya, Depok. Primary data was obtained using a questionnaire research instrument with 90 MSME respondents, and processed using SPSS. Research results show the influence of business digitalization on the competitive advantage and resilience of MSMEs in Sukmajaya, Depok. MSMEs in Sukmajaya can achieve MSMEs resilience by optimizing business digitalization and increasing its competitive advantage during the post-covid 19 pandemic period and after.